Acute Oral Toxicity studies on Ethanol Extract of Aerial Parts of Blumea laevis (EABL) in Rats - Kumar, Yashas R.; Nair, Divakaran N.; R., Anoopraj; K.S., Prasanna; Palekkodan, Hamza; George, Ajith Jacob; Rani, Suja (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Acute toxicity test of ethanol extract of aerial parts of Blumea laevis (EABL) plant material was studied in female Sprague-Dawley rats owing to lack of studies on toxicity of B. laevis plant. The in-vivo acute oral toxicity EABL in Sprague Dawley rats was carried out as per OECD guidelines 425. Results revealed that there was no significant difference (p>0.05) in feed intake in both the treatment groups (i.e., 1750 & 5000 mg/kg) even though water intake was significantly higher (p<0.01) in animals receiving 5000 mg/ kg of EABL as compared to 1750 mg/ kg body weight. There was an increase in body weight was observed in animals receiving 5000 mg/ kg as compared to treatment at 1750 mg/Kg. Furthermore, animals did not produce toxic effects on signs, general behavior, mortality and gross appearance of internal organs of rats during the 14-day observation period. Hence the LD50 of EABL was found to be more than 5000 mg/Kg body weight. In conclusion, to the best of our literature knowledge this is the preliminary pilot study to demonstrate EABL did not cause toxicity in oral acute studies in rats and was found to be safer. However, additional studies in sub-acute and chronic toxicity evaluation are needed to further determine the long-term safety of this plant extract.